2017
DOI: 10.1002/ece3.3392
|View full text |Cite
|
Sign up to set email alerts
|

Keystone nonconsumptive effects within a diverse predator community

Abstract: The number of prey killed by diverse predator communities is determined by complementarity and interference among predators, and by traits of particular predator species. However, it is less clear how predators' nonconsumptive effects (NCEs) scale with increasing predator biodiversity. We examined NCEs exerted on Culex mosquitoes by a diverse community of aquatic predators. In the field, mosquito larvae co‐occurred with differing densities and species compositions of mesopredator insects; top predator dragonfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 76 publications
2
7
0
Order By: Relevance
“…We found that indirect non-consumptive effects of fish cues decreased survival to emergence and the development time to emergence in the damselfly. These results correspond with those from previous studies (Tseng 2003, Hellmann et al 2011, McCauley et al 2011, Meadows et al 2017 and, thus, further confirm that indirect non-consumptive effects are present in many animals with complex life cycles (Benard 2004). The novelty of our experiment was that we looked across 3 developmental stages: eggs, larvae, and adults.…”
Section: Discussionsupporting
confidence: 91%
“…We found that indirect non-consumptive effects of fish cues decreased survival to emergence and the development time to emergence in the damselfly. These results correspond with those from previous studies (Tseng 2003, Hellmann et al 2011, McCauley et al 2011, Meadows et al 2017 and, thus, further confirm that indirect non-consumptive effects are present in many animals with complex life cycles (Benard 2004). The novelty of our experiment was that we looked across 3 developmental stages: eggs, larvae, and adults.…”
Section: Discussionsupporting
confidence: 91%
“…Predators of vectors can prevent pathogen establishment in naïve host populations, and the introduction of a vector predator into a host-vector-parasite system at equilibrium can extirpate pathogens through vector population regulation (Moore, Borer, & Hosseini, 2009). Non-consumptive effects of predators on the vector Culex can also decrease vector density by decreasing survival to pupation, adult size, and longevity (Meadows, Owen, & Snyder, 2017).…”
Section: A Susceptible Host or Vector Density At The Disease-free Equilibrium (S* H* Or V*)mentioning
confidence: 99%
“…Alternatively, even when defensive responses appear to conflict, the presence of multiple predators may sometimes improve prey survival. For example, Meadows et al (2017) showed that Culex mosquito larvae respond to a complex of mesopredators by diving towards the bottom of water bodies; however, in the presence of top predators, dragonfly larvae, which forage lower in the water column, diving responses by Culex are suppressed. Because the diving behaviour is costly, suppression of this response doubled the survival of larval mosquitoes to pupation.…”
Section: Effects Of Multiple Enemies On Pestsmentioning
confidence: 99%